(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The growth accounting equation is totally free from all kinds of measurement units and is expressed with pure numbers. (i.e. growth rates and elasticity’s) eliminating the effects of inflation etc. Still, it does not measure the true contribution rather just distributes the growth in labor, capital and technical change. The value of total factor productivity is not measured but its growth is assessed. At the aggregate industry level data, the total factor productivity growth shows the changing quality of political, legal, administrative, infrastructure and knowledge systems of the economy. There is a need to break the total factor productivity into various other causes through further research.If the study is conducted at individual industry levels then various elasticities of output for each industry can be computed separately and can be compared to identify those industries and technologies, which augment employment growth. Then the state can focus to nurture those industries, which add to faster employment growth than the growth rate of labor force generation to include one and all in sharing fruits of economic liberalization.